Overview of Salmonella Genomic Island 1-Related Elements Among Gamma-Proteobacteria Reveals Their Wide Distribution Among Environmental Species - Siebor, Eliane; Neuwirth, Catherine (Frontiers in Microbiology, 2022)
The aim of this study was to perform an in silico analysis of available whole-genome sequencing data to detect syntenic genomic islands (GIs) with homology to Salmonella genomic island 1 (SGI1), analyze the genetic variations of their backbone and determine their relatedness. Eighty-nine non-redundant SGI1-related elements (SGI1-REs) were identified among gamma-Proteobacteria. With the inclusion of the thirty-seven backbones characterized to date, seven clusters were identified based on integrase homology: SGI1, PGI1, PGI2, AGI1 clusters, and clusters 5, 6 and 7 composed of GIs mainly harbored by waterborne or marine bacteria, such as Vibrio, Shewanella, Halomonas, Idiomarina, Marinobacter and Pseudohongiella. The integrase genes and backbones of SGI1-REs from clusters 6 and 7, and from PGI1, PGI2 and AGI1 clusters differed significantly from those of SGI1 cluster, suggesting a different ancestor. All backbones consisted of two parts: the part from attL to oriT harbored the DNA recombination, transfer, and mobilization genes, and the part from oriT to attR differed between clusters. The diversity of SGI1-REs resulted from recombination events between GIs of the same or other families. oriT appeared to be a high recombination site. The MDR region was located upstream of the resolvase gene. However, most SGI1-REs in Vibrio, Shewanella and marine bacteria did not harbor any MDR region. These strains could constitute a reservoir of SGI1-REs that could be potential ancestors for pathogenic bacteria. Furthermore, four SGI1-REs did not harbor a resolvase gene and therefore could not acquire an integron. The presence of mobilization genes and AcaCD binding sites indicated that their conjugative transfer could occur with helper plasmids. The plasticity of SGI1-REs contributes to bacterial adaptation and evolution. We propose a more relevant classification to categorize SGI1-REs into different clusters based on their integrase gene similarity.